Nano Cyclotetramethylene Tetranitramine Particles Prepared by a Green Recrystallization Process. Issue 5 (14th July 2014) - An, Chongwei; Li, Hequn; Guo, Wenjian; Geng, Xiaoheng; Wang, Jingyu
Abstract The solubility of cyclotetramethylene tetranitramine (HMX) in four ionic liquids (ILs): 1, 3‐dimethylimidazolium dimethylphosphate ([Memim]DMP), 1‐butyl‐3‐methylimidazolium chloride ([Bmim]Cl), 1‐hexyl‐3‐methylimidazolium bromide ([Hmim]Br), and 1‐ethyl‐3‐methylimidazolium tetrafluoroborate ([Emim]BF4) was investigated. Nano‐HMX were produced particles by spraying [Hmim]Br solution into purified ice water. Finally, the particle size, morphology, crystal phase, impact sensitivity, and thermal decomposition properties of nano‐HMX particles were tested and analyzed. All four ILs could dissolve HMX to a greater or lesser extent in the temperature range from 20 °C to 80 °C. The solubility of HMX in [Hmim]Br at 80 °C is up to 0.7 g mL−1. Recrystallized HMX particles are of polyhedral or spherical shape and 40 to 130 nm in size. X‐ray diffraction indicated that nano‐HMX has a similar crystal structure as raw HMX (β‐form). Compared with raw HMX, the nano‐HMX particles have much lower impact sensitivity. However, they are easier to explode than raw HMX under thermal stimulus due to the lower peak temperature and activation energy.